2021
DOI: 10.1057/s42984-020-00029-4
|View full text |Cite
|
Sign up to set email alerts
|

How did Russian and Iranian trolls’ disinformation toward Canadian issues diverge and converge?

Abstract: The study analyzes Russian and Iranian trolls' intervention in Canadian politics focusing on the 2015 election, revealing a wide spectrum of disinformation. Russian trolls showed some support for then prime minister Stephen Harper and were very critical of the current prime minister, Justin Trudeau. Also, they closely aligned themselves with conservative and far-right figures, while Iranian trolls supported the far left as well as the Palestinian cause. Iranian trolls frequently attacked the former prime minis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…O'Connor et al found that between 2010 and 2020, Russia used online disinformation to interfere with ''31 elections and seven referendums involving 26 states'' including members of the EU, the USA, nations of Africa and South America, as well as Canada [58]. Russia, especially through the IRA, used social media disinformation to target both Canadian elections and Canadian society, promoting Stephen Harper and denigrating Justin Trudeau, while fiercely encouraging right-wing extremism, particularly via amplifying and fomenting Islamophobia and antiimmigrant hatred [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O'Connor et al found that between 2010 and 2020, Russia used online disinformation to interfere with ''31 elections and seven referendums involving 26 states'' including members of the EU, the USA, nations of Africa and South America, as well as Canada [58]. Russia, especially through the IRA, used social media disinformation to target both Canadian elections and Canadian society, promoting Stephen Harper and denigrating Justin Trudeau, while fiercely encouraging right-wing extremism, particularly via amplifying and fomenting Islamophobia and antiimmigrant hatred [47].…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate, in 2019, the European Commission released a progress report on its Action Plan Against Disinformation. According to the Commission, evidence gathered throughout 2018 and early 2019 confirmed ongoing disinformation activities originating from Russian sources, believed to be undertaken for the purpose of influencing voter preferences and suppressing voter turnout in the EU Parliamentary elections [22,47]. A recent study of Canadian Twitter data suggests that Russian trolls were behind ''fake news'' stories that attempted to stoke fear and distrust between Muslims and non-Muslims following the 2017 shooting deaths of six worshippers at a mosque in Quebec City, leading to renewed concerns that Russian trolls might attempt to interfere in the Fall 2019 Canadian federal election [48,49].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research in this area continues to be limited. Al-Rawi (2021) examined Russian Twitter trolls and their role in spreading disinformation during the 2015 Canadian Federal election. The study found that Russian Twitter trolls showed significant support for Stephen Harper (the Conservative Party representative) and were hyper-critical of Justin Trudeau (the Liberal Party representative).…”
Section: Canadamentioning
confidence: 99%
“…Third, RT (# 312 in Alexa), formerly known as Russia Today, had a clear lead in both periods. Russia Today is a state-owned media outlet well known for disinformation [13,14] and supporting Russian diplomatic goals as an information warfare tool [15].…”
Section: Beforementioning
confidence: 99%